Harry Payne Whitney collection of letters of William Collins Whitney - Whitney, William C. (William Collins), 1841-1904.; Whitney, Harry Payne, 1872-1930.
Correspondence; business, legal, and financial records; genealogies; scrapbooks; printed matter; photographs; and other papers pertaining chiefly to William C. Whitney's service as corporation counsel in the New York (N.Y.) Law Dept. and as U.S. secretary of the navy in the first Grover Cleveland presidential administration. Documents his work in the modernization of the U.S. Navy and his fight against political corruption and fraud in New York, N.Y., primarily in relation to Tammany Hall and the Tweed Ring. Subjects include New York city and state politics; the Democratic Party (N.Y); national politics; and foreign relations. Other subjects include Grover Cleveland's nomination and election as New York state governor and U.S. president; presidential campaigns, 1884-1896; bimetallism; silver question; tariff; social life in New York, N.Y., and Washington, D.C.; horse racing: yachting: and Whitney family affairs. Includes six scrapbooks containing photographs from the Lady Franklin Bay Expedition (1881-1884) led by A.W. Greely.
Library of Congress Prints and Photographs Division.
U.S. secretary of the navy, financier, and sportsman.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Cleveland, Grover, -- 1837-1908.; Greely, A. W. -- 1844-1935.; Whitney family; New York (N.Y.). -- Law Department; United States. -- Navy; United States. -- Navy Department; Tammany Hall; Bimetallism; Fraud -- New York (State) -- New York; Genealogy; Horse racing; Political corruption -- New York (State) -- New York; Presidents -- United States -- Election; Silver question; Tariff; Tweed Ring; Yachting; Arctic regions -- Discovery and exploration; New York (N.Y.) -- Politics and government -- To 1898.; New York (N.Y.) -- Social life and customs; New York (State) -- Politics and government -- 1865-1950.; Polar regions -- Discovery and exploration; United States -- Foreign relations -- 1865-1898.; United States -- Politics and government -- 1865-1900.; Washington (D.C.) -- Social life and customs; Cabinet officers; Financiers; Sportsmen